Teknik Reduksi pada Penerjemahan Kalimat Imperatif dan Nominal Arab-Indonesia - Ade Irma; Ubaidillah (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2023)
Language is a means of communication that humans use to communicate with each other both orally and through text. A translation process is needed so that the listener or reader can understand the intent of the speaker or writer. This research aims to explain the use of reduction techniques in translating Arabic imperative sentences and Arabic nominal sentences into Indonesian by analyzing in terms of I’rab, syntax function and syntax category, as well as the pattern used in translation. This research can add insight to the reader and person who wants to be a translator (Arabic language into the Indonesian language) by giving a detailed explanation regarding reduction techniques and their use in imperative and nominal sentences. The method used, namely qualitative descriptive with a case study from some Arabic sentences that changed the form of reduced syntax functions when translated into the Indonesian language. Through this research, it is known that the reduction technique for solving the Arabic language into the Indonesian language needs to use because of the existence of the second person pronoun (the person being spoken/dhamir mukhatab) no need to mention in Indonesian imperative sentences. The same goes for nominal sentences; reduction technique is used based on the assumption that a syntactic function in Arabic as the source language is not always required in Indonesian as the receiving language.